Improving Ship Loading and Unloading Efficiency Through Optimizing Cargo Control Room Operations - K.P. Suharyono S. Hadiningrat; Rico Suji Asmoro; Verry Albert Jekson Mardame Silalahi (PT. Pustaka Cendekia Publisher, 2025)
Loading and unloading efficiency is a critical aspect of ship operations, which has a significant impact on operational costs, customer satisfaction, and the competitiveness of shipping companies. The Cargo Control Room (CCR) acts as a control center that optimizes the loading and unloading process through integrated technology and systems. However, the operation of CCR faces various challenges, such as technical issues, coordination between parties, and limited human resources (HR). This study aims to analyze the optimization strategy of CCR operations to improve the efficiency of loading and unloading on ships. The research method used is qualitative descriptive with a literature study approach, collecting data from journal articles, books, and related technical reports. The results show that CCR optimization can be achieved through the use of the latest technology such as automation, Internet of Things (IoT), and real-time monitoring systems, human resource training and development, and improved coordination between departments. The impact of this optimization includes reduced loading and unloading times, minimization of errors and operational risks, and an increase in overall productivity. The conclusion of this study confirms that technology integration, improvement of human resource competence, and good coordination are key factors in optimizing the operation of CCR. This study recommends the need for further empirical research to test the findings of literature studies as well as the implementation of technology and continuous training for CCR operators.